2020
DOI: 10.3390/cells9081885
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke Risk Associated with Mitochondrial Haplogroup F in the Asian Population

Abstract: Mitochondrial dysfunction is involved in the pathogenesis of atherosclerosis, the primary risk factor for ischemic stroke. This study aims to explore the role of mitochondrial genomic variations in ischemic stroke, and to uncover the nuclear genes involved in this relationship. Eight hundred and thirty Taiwanese patients with a history of ischemic stroke and 966 normal controls were genotyped for their mitochondrial haplogroup (Mthapg). Cytoplasmic hybrid cells (cybrids) harboring different Mthapgs were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…The production of ROS in mitochondria can depend on mitochondrial gene expression. Using RNA sequencing, it was shown that the mitochondrial haplogroup F1 (Mthapg F1)-encoding gene was overexpressed in patients with ischemic stroke and that Mthapg F1 upregulation induced ROS production in mitochondria and decreased cell viability ( Tsai et al, 2020 ). NADPH oxidase 2 (NOX2) is considered an important enzyme catalyzing ROS formation in the brain.…”
Section: Mechanisms Of Ferroptosis In the Pathogenesis Of Ischemic Strokementioning
confidence: 99%
“…The production of ROS in mitochondria can depend on mitochondrial gene expression. Using RNA sequencing, it was shown that the mitochondrial haplogroup F1 (Mthapg F1)-encoding gene was overexpressed in patients with ischemic stroke and that Mthapg F1 upregulation induced ROS production in mitochondria and decreased cell viability ( Tsai et al, 2020 ). NADPH oxidase 2 (NOX2) is considered an important enzyme catalyzing ROS formation in the brain.…”
Section: Mechanisms Of Ferroptosis In the Pathogenesis Of Ischemic Strokementioning
confidence: 99%
“…In studying the role of TAZ in ferroptosis in ovarian cancer, angiopoietin like 4 was found to be a direct target gene regulated by TAZ, sensitizing ferroptosis through activation of NOX2 ( Yang et al, 2020b ). More importantly, ANGPTL4 maintains the integrity of the vascular endothelium by regulating vascular permeability, angiogenesis, inflammatory signaling, oxidative stress and lipid metabolism ( Guo et al, 2014 ; Tsai et al, 2020 ). In addition, ANGPTL4 also regulates cellular energy homeostasis and reactive oxygen species and has been implicated in the pathogenesis of AS, including endothelial dysfunction, LDL oxidation and nitric oxide reduction ( Zhu et al, 2012 ; Tsai et al, 2020 ).…”
Section: Signaling Pathways Of Ferroptosis Associated With Atherosclerosismentioning
confidence: 99%
“…More importantly, ANGPTL4 maintains the integrity of the vascular endothelium by regulating vascular permeability, angiogenesis, inflammatory signaling, oxidative stress and lipid metabolism ( Guo et al, 2014 ; Tsai et al, 2020 ). In addition, ANGPTL4 also regulates cellular energy homeostasis and reactive oxygen species and has been implicated in the pathogenesis of AS, including endothelial dysfunction, LDL oxidation and nitric oxide reduction ( Zhu et al, 2012 ; Tsai et al, 2020 ). Hepatic ANGPTL4 deficiency significantly reduces triacylglycerol (TAG) and cholesterol levels, providing some protection against AS ( Singh et al, 2021 ).…”
Section: Signaling Pathways Of Ferroptosis Associated With Atherosclerosismentioning
confidence: 99%
“…Our group has reported that the haplotype B4 (carrying the T16189C variant) is associated with T2DM (odds ratio [OR], 1.54 [95% CI 1.18–2.02]; P < 0.001) in the Chinese population, whereas subjects harboring haplogroup D4 have borderline resistance against DM generation (0.68 [0.49–0.94]; P = 0.02) ( Liou et al, 2010 ). Recently, a patient study with 830 Taiwanese ischemic stroke patients and 966 normal controls revealed an association between mitochondrial haplogroup F1 and risk of ischemic stroke (OR 1.72:1.27–2.34, p = 0.001) ( Tsai et al, 2020 ). In the same study, with the usage of a hybrid technique, Tsai et al (2020) demonstrated that mitochondrial haplogroup F1 cybrids were associated with decreased oxygen consumption, higher mitochondrial ROS production, and lower mitochondrial membrane potential.…”
Section: Association Of Cardiovascular Diseases and Mitochondrial Dysmentioning
confidence: 99%
“…Recently, a patient study with 830 Taiwanese ischemic stroke patients and 966 normal controls revealed an association between mitochondrial haplogroup F1 and risk of ischemic stroke (OR 1.72:1.27–2.34, p = 0.001) ( Tsai et al, 2020 ). In the same study, with the usage of a hybrid technique, Tsai et al (2020) demonstrated that mitochondrial haplogroup F1 cybrids were associated with decreased oxygen consumption, higher mitochondrial ROS production, and lower mitochondrial membrane potential. These cybrids were also noted to be prone to inflammation, with increased expression of several inflammatory cytokines.…”
Section: Association Of Cardiovascular Diseases and Mitochondrial Dysmentioning
confidence: 99%